Effect of a "lean" intervention to improve safety processes and outcomes on a surgical emergency unit - McCulloch, P; Kreckler, S; New, S; Sheena, Y; Handa, A; Catchpole, K (BMJ Publishing Group, 2010)
Problem Emergency surgical patients are at high risk for harm because of errors in care. Quality improvement methods that involve process redesign, such as “Lean,” appear to improve service reliability and efficiency in healthcare. Design Interrupted time series. Setting The emergency general surgery ward of a university hospital in the United Kingdom. Key measures for improvement Seven safety relevant care processes. Strategy for change A Lean intervention targeting five of the seven care processes relevant to patient safety. Effects of change 969 patients were admitted during the four month study period before the introduction of the Lean intervention (May to August 2007), and 1114 were admitted during the four month period after completion of the intervention (May to August 2008). Compliance with the five process measures targeted for Lean intervention (but not the two that were not) improved significantly (relative improvement 28% to 149%; P<0.007). Excellent compliance continued at least 10 months after active intervention ceased. The proportion of patients requiring transfer to other wards fell from 27% to 20% (P<0.000025). Rates of adverse events and potential adverse events were unchanged, except for a significant reduction in new safety events after transfer to other wards (P<0.028). Most adverse events and potential adverse events were owing to delays in investigation and treatment caused by factors outside the ward being evaluated. Lessons learnt Lean can substantially and simultaneously improve compliance with a bundle of safety related processes. Given the interconnected nature of hospital care, this strategy might not translate into improvements in safety outcomes unless a system-wide approach is adopted to remove barriers to change.